Gastrointestinal stromal tumor: Role of surgery and immunotherapy - Bhatnagar Sushmita (Wolters Kluwer Medknow Publications, 2010)
Report of a gastrointestinal stromal tumor in an 11-year-old girl who presented with a large lump in the upper abdomen. After complete surgical excision and histopathology, postoperative immunotherapy with imatinib led to an excellent outcome and a tumor-free survival of 3 years.